2019
DOI: 10.1080/03009742.2019.1570549
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of sick leave and improved worker productivity after 52 weeks of intensive treatment in patients with early rheumatoid arthritis

Abstract: Objective: To identify predictors of sick leave and improved worker productivity in patients with early rheumatoid arthritis (RA) treated for 52 weeks with intensive combination strategies. Methods: Patients with early RA were included in the COmbinatietherapie Bij Reumatoïde Artritis (COBRA)-light trial and followed for 52 weeks. As the COBRA-light strategy proved to be non-inferior to the COBRA strategy, all patients were pooled. Predictors for sick leave and improved worker productivity were assessed throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…In addition, reduced pain intensity has been reported to significantly correlate with improved work productivity (35), and improved grip force has been connected to improved work ability (36). Previous research also shows that a strong predictor for sickness absence is earlier sickness absence (12,37). Furthermore, the earlier biological treatment starts, the greater the possibility of returning to work (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, reduced pain intensity has been reported to significantly correlate with improved work productivity (35), and improved grip force has been connected to improved work ability (36). Previous research also shows that a strong predictor for sickness absence is earlier sickness absence (12,37). Furthermore, the earlier biological treatment starts, the greater the possibility of returning to work (38).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research reports that disease activity (8,9) and activity limitation (10,11) are connected to a patient's ability to continue working. However, Blomjous et al (12) reported that sickness absence and worker productivity of people diagnosed with early RA are mainly predicted by nondisease-specific variables. That is, sickness absence due to RA is multifactorial.…”
mentioning
confidence: 99%
“…The following demographic data were collected as assessed for the Amsterdam SLE cohort: age, ethnicity and highest attained educational level, stratified into low (<12 years), intermediate (12–16 years) and high (≥17 years) [ 24 , 26 ]. Disease-related variables collected were disease duration (at the time of completing the questionnaire), Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI) and history of lupus nephritis.…”
Section: Methodsmentioning
confidence: 99%